Model Tests of the Influence of Excavation Unloading and Servo Loading on Subway Foundation Pits - Gang Wei; Weihao Feng; Xuehua Wu; Pengfei Wu; Kuan Chang; Hang Li; Shuaihua Ye; Zhe Wang (Buildings)
In deep foundation pit engineering, the rational arrangement of internal struts plays a crucial role in controlling diaphragm wall displacement and minimizing environmental impacts. This study investigates the effects of servo steel struts through model tests, analyzing diaphragm wall displacement, bending moment, surface settlement, and surrounding soil pressure during both excavation and active servo control phases. The results show that installing servo struts near the pit bottom significantly improves deformation control, whereas strut placement in shallow zones more effectively mitigates surface settlement. The servo system dynamically adjusts strut displacements, thereby inducing internal force redistribution in the diaphragm wall and modifying the stress field in surrounding soils. This mechanism leads to an increase in positive bending moments on the wall’s backside, which may necessitate the localized reinforcement of the diaphragm wall at servo strut connections to ensure structural integrity. The lateral wall and surrounding soil pressure exhibit further increase, effectively compensating for the pressure loss induced by excavation unloading. Notably, the influence on soil pressure demonstrates a dissipating trend with an increasing distance from the excavation.